2014
DOI: 10.1063/1.4893702
|View full text |Cite
|
Sign up to set email alerts
|

Vibrationally specific photoionization cross sections of acrolein leading to the $\tilde{X}\,{}^2\!A^{\prime }$X̃A′2 ionic state

Abstract: The vibrational branching ratios in the photoionization of acrolein for ionization leading to the X̃²A' ion state were studied. Computed logarithmic derivatives of the cross section and the corresponding experimental data derived from measured vibrational branching ratios for several normal modes (ν9, ν10, ν11, and ν12) were found to be in relatively good agreement, particularly for the lower half of the 11-100 eV photon energy range considered. Two shape resonances have been found near photon energies of 15.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…Calculated total rate constants for O + DME and O + four methyl esters (MHX = methyl hexanoate, MPE = methyl pentanoate, MB = methyl butanoate, MPR = methyl propanoate). The present results (solid lines) are compared with the 1DHR calculations (dashed lines) for DME (present work) and MPR (taken from ref ) and with an experimentally derived Arrhenius expression (●) for DME.…”
Section: Theorysupporting
confidence: 47%
See 1 more Smart Citation
“…Calculated total rate constants for O + DME and O + four methyl esters (MHX = methyl hexanoate, MPE = methyl pentanoate, MB = methyl butanoate, MPR = methyl propanoate). The present results (solid lines) are compared with the 1DHR calculations (dashed lines) for DME (present work) and MPR (taken from ref ) and with an experimentally derived Arrhenius expression (●) for DME.…”
Section: Theorysupporting
confidence: 47%
“…For larger species with unknown photoionization cross sections, every effort was made to remove all experimental factors, as discussed in detail in refs and . Although photoionization cross sections can be calculated theoretically, , it has been demonstrated that the uncertainty is substantial for large molecules, resulting in the data being less useful for future model comparisons and validation. Instead, we present these data in the Supporting Information as mole fraction x cross section as seen in Figure for the ketohydroperoxide (C 7 H 15 O 5 ).…”
Section: Methodsmentioning
confidence: 99%